Analysis of the results of a diagnostic test of previous knowledge in the area of mathematics in a Colombian rural Educational Institution - Orozco-Carvajal, Carlos A. (2023)
The quality of education in Colombia today is confirmed by the standardized test designed and applied by the Colombian Institute for the Evaluation of Education (ICFES) to all students in the country at different levels. The purpose of this article is to analyze the results of a  diagnostic test of previous knowledge designed by the ICFES in the area of mathematics applied to all high school and middle school students of the San Antonio del Pescado Educational Institution (IESAP), located in the rural area of the municipality of Garzon (Huila). Among the aspects found is the parallelism of the tests applied to eleventh grade students in the last five years with respect to the diagnostic test conducted at the beginning of the 2022 school year. Similarly, some of the effects of the pandemic are specified, such as grade repetition and school dropout, together with the lack of accompaniment and follow-up by the state to improve the educational conditions of the students. It also analyzes the importance and relationship between knowledge, the teacher and the student (didactic triangle) and the opportunity to use mathematical competencies from an integral perspective frome its three dimensions that are connected with the six primary knowledge of Romero (2019) to tend in a didactic way to increase not only the results of standadized test, but also to develop competencies for the future life of students.